The making of a mushroom: Mitosis, nuclear migration and the actin network - Jung E.; Kothe E.; Raudaskoski M. (Academic Press Inc., 2022)
Basidiomycetes feature a prolonged dikaryotic life stage. A dispute over open versus closed mitosis could be
solved using in vivo fluorescence videomicroscopy of histone 2B::EGFP and Lifeact labeled Schizophyllum commune.
It revealed nuclei to condense to approximately one fifth in diameter during mitotic prophase. In addition,
the specifics of clamp cell formation typical of many basidiomycetes included an actin network at the future site
of nuclear division, which allowed for cessation of nuclear movement and re-localization of one nucleus towards
the emerging clamp cell, while the other divided along the hyphal axis. Subsequent fusion of the clamp cell to
form the clamp connection restored the close association of the two nuclei in a very fast process after clamp
fusion. Septation was preceded by actin patches and vesicles involved in formation of the actin ring.